2015
DOI: 10.1186/s11689-015-9111-z
|View full text |Cite
|
Sign up to set email alerts
|

Memory in language-impaired children with and without autism

Abstract: BackgroundA subgroup of young children with autism spectrum disorders (ASD) have significant language impairments (phonology, grammar, vocabulary), although such impairments are not considered to be core symptoms of and are not unique to ASD. Children with specific language impairment (SLI) display similar impairments in language. Given evidence for phenotypic and possibly etiologic overlap between SLI and ASD, it has been suggested that language-impaired children with ASD (ASD + language impairment, ALI) may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 71 publications
3
33
0
Order By: Relevance
“…These findings are consistent with proposals related to impaired phonological memory in ASD based on non-word repetition effects (e.g. [15]). While the data indicate that phonological processing is atypical, they do not license conclusions about behavioral consequences of these differences.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with proposals related to impaired phonological memory in ASD based on non-word repetition effects (e.g. [15]). While the data indicate that phonological processing is atypical, they do not license conclusions about behavioral consequences of these differences.…”
Section: Discussionsupporting
confidence: 92%
“…Disordered speech perception is not a typical symptom of ASD [13, p. 125], although impairments in repeating novel words has been linked with deficits in phonological memory which may have perceptual consequences (e.g. [14, 15]). However, Whitehouse & Bishop [16], using Event-Related Potentials (ERP) and an oddball paradigm, observe that altered neural responses to speech sounds reflect disrupted top-down modulation and not bottom-up sensory effects.…”
Section: Introductionmentioning
confidence: 99%
“…Participants' WM scores (M = 7.1, SD = 1.68, range = 4-11) were converted from raw to scaled scores with a mean of 10 and standard deviation of 3 (Hill, van Santen, Gorman, Langhorst & Fombonne, 2015). According to self-reported questionnaire data, the average age at which participants' second language was acquired was 7.1 years (SD = 2.85, range = 1.5-12).…”
Section: Predictors Of Speech Reception Thresholdsmentioning
confidence: 99%
“…Contrary to the profiles typically seen in children with SLI, several studies have reported that individuals with ASD had visuospatial WM deficits but no verbal WM deficits [4749]. Conversely, other studies have found deficits in verbal WM in children with ASD [7, 14] or deficits in both spatial and verbal WM [50, 51]. Williams and colleagues [51] found that the memory profile in children with ASD was characterized by deficits in complex visual and verbal memory as well as spatial WM.…”
Section: Introductionmentioning
confidence: 99%